(untitled) (International Journal of Advanced Research in Computer Science, 2017)
A penetration test is performed on an operating system with the expectation of discovering security weaknesses and exploiting target OS. The goal of this testing is to find all security vulnerabilities without any type of actually harming the computer system. In this research paper, we discuss the some phases of penetration testing on operating system. We are using some tools and techniques to penetrate the target system by using Nmap, Metasploit (msfconsole) and Meterpreter. We will make remove folders in host OS and also make and delete folders to the target OS through LINUX commands. And we will shut down the target operating system with using Linux commands. In this, we are using penetration testing tool to attack on particular operating system and to scan and also exploiting target OS. In the previous research paper, we had performed the work on scanning the target operating system with reconnaissance tool Nmap. In this research paper, we will work only on exploitations of our target operating system with Windows XP SP0 â€œService Packâ€. Keywords: Penetration Testing, VMware, Kali Linux, Nmap, Scanning, Metasploit, Meterpreter, Exploitation, msfconsole.